Optimization Study of PVT Coupled Water Loop Heat Pump Energy Supply System - Lv Tiangang; Liu Bing; Wu Jun; Zhu Li; Hou Jingxuan (E3S Web of Conferences)
Building energy consumption accounts for a large proportion of total global energy consumption, and heating and air conditioning energy consumption is a key control point for building energy efficiency. Coupling water-loop heat pumps with PVT system can improve system stability and increase building energy efficiency. This study designs a building energy supply system integrating PVT and a water-loop heat pump based on Tianjin's meteorological data, using TRNSYS software to establish a dynamic model. By employing the Hooke-Jeeves algorithm, the system's design and operation parameters were optimized with annual cost and system COP as objective functions. Design variables included PVT inclination, azimuth, area, heat pump capacity, and tank volume, while operational variables were PVT backplate temperature and tank temperature. Results indicate optimal settings: PVT inclination at 44.8°, azimuth at 3.8°, area of 213.7 m2, heat pump capacity of 118.4 kW, and tank volume of 8.6 m3, reducing annual costs by 6.01%. Operationally, T1-T2 limits are 8℃ (upper) and 3℃ (lower), while T2 ranges from 15℃ to 47℃, achieving the highest COP, with a 4%- 6% improvement compared to pre-optimization.